Levels of Bisphenol A and its analogs in nails, saliva, and urine of children: a case control study - Gálvez-Ontiveros, Yolanda; Moscoso-Ruiz, Inmaculada; Almazán Fernández de Bobadilla, Vega; Monteagudo, Celia; Giménez-Martínez, Rafael; Rodrigo, Lourdes; Zafra-Gómez, Alberto; Rivas, Ana (Frontiers in Nutrition, 2023)
A growing number of studies link the increase in overweight/obesity worldwide to exposure to certain environmental chemical pollutants that display obesogenic activity (obesogens). Since exposure to obesogens during the first stages of life has been shown to have a more intense and pronounced effect at lower doses, it is imperative to study their possible effects in childhood. The objective here was to study the association of Bisphenol A (BPA) and 11 BPA analogues in children, using three biological matrices (nails, saliva and urine), and overweight and obesity (n= 160). In this case-control study, 59 overweight/obese children and 101 controls were included. The measuring of Bisphenols in the matrices was carried out by ultra-high performance liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UHPLC-MS/MS). Logistic regression was used to study the association between overweight/obesity and Bisphenol exposure. The results suggested that BPF in nails is associated with overweight/obesity in children (OR:4.87; p= 0.020). In saliva, however, the highest detected concentrations of BPAF presented an inverse association (OR: 0.06; p= 0.010) with overweight/obesity. No associations of statistical significance were detected between exposure to BPA or its analogues and overweight/obesity in any of the biological matrices.